Faktor - Faktor yang Mempengaruhi Bounding Attachment Masa Nifas - Dewi Susilawati; Nur Fadjri Nilakesuma; Risnawati Risnawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the factors that affect puerperal breastfeeding attachment. The research method used was descriptive-analytic research with a cross-sectional design. The study results describe the variables of maternal characteristics (age, education, and parity) that affect the bounding attachment, with only parity variables with p values of 0.041. In addition, the effect on bounding attachment is the parent / family response variable (p = 0.036) and social support (p = 0.029) while there is no influence of the level of knowledge with bounding attachment (p = 1,000). In conclusion, socialize bounding attachment to mothers, families, the community to increase mother's knowledge and increase the success of Bounding Attachments between mother and child. Keywords: Bounding Attachment, Postpartum Mother, Postpartum Bonding Questionnaire (PBQ)